Diagnose and investigation of angular distribution of copper plasma ions - Noriah Bidin, 1957-, author; Yaacob Mat Daud; Ieee Regional Symposium on Nvcroeletonics (2007 : pulau Pinang)ns (3th : 2007 : Pulau Pinang) (Skudai : Universiti Teknologi Malaysia, 2007)
PRZSL